2017
DOI: 10.13057/biodiv/d180331
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of the mangrove species Avicennia marina in heavy metal polluted estuaries of Cilegon Industrial Area, Indonesia

Abstract: Manurung J, Siregar IZ, Kusmana C, Dwiyanti FG. 2017. Genetic variation of the mangrove species Avicennia marina in heavy metal polluted estuaries of Cilegon Industrial Area, Indonesia. Biodiversitas 18: 1109-1115. Mangrove forests are often facing various anthropogenic disturbances, particularly in the industrial area. However, information on the status of industrial heavy metal pollution and its impact on the genetic variation of mangrove species, such as Avicennia marina, particularly in Indonesian industri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…Megalurus palustris, Lonchura leucogastroides, Pycnonotus aurigaster, and Passer montanus are indicators of open and disturbed habitat. Suryawan et al (2017) said that Passer montanus is commonly found around the housing of residents in villages. These species have a high tolerance level to the presence and interference of humans, indicated by their ability to make nests in residential and development areas.…”
Section: Birds As Indicators In Ecosystemmentioning
confidence: 99%
“…Megalurus palustris, Lonchura leucogastroides, Pycnonotus aurigaster, and Passer montanus are indicators of open and disturbed habitat. Suryawan et al (2017) said that Passer montanus is commonly found around the housing of residents in villages. These species have a high tolerance level to the presence and interference of humans, indicated by their ability to make nests in residential and development areas.…”
Section: Birds As Indicators In Ecosystemmentioning
confidence: 99%
“…Some mangrove species could even grow in places with high salinity level. For example, Avicennia marina can grow in high salinity water (Manurung et al 2017). Salinity condition of Tarus mangrove location can be seen in Figure 2.…”
Section: Physicochemical Conditions Of Mangrove Forest At Tarusmentioning
confidence: 99%
“…An older technology that is still relevant and can be used to assess genetic diversity in plants is RAPD. RAPD is a DNA-based method that has widely used for a variety of purposes, such as genetic diversity (Manurung et al 2017), selection of cultivars of the genetic character of salttolerant (Juwarno and Samiyarsih 2017), conservation of cultivars as local genetic resources (Herawati et al 2018) and genetic diversity-genetic variation of species (Annisa et al 2019).…”
Section: Introductionmentioning
confidence: 99%